Colorimetric Determination Of Hydrogen Peroxide Based on Localized Surface Plasmon Resonance of Silver Nanoprisms Using a Microchannel Chip. (13th August 2019) - Lertvachirapaiboon, Chutiparn; Kiyokawa, Itaru; Baba, Akira; Shinbo, Kazunari; Kato, Keizo
Abstract: Silver nanoprisms (AgNPrs) have unique optical phenomena due to their localized surface plasmon resonance that results in the extinction of light from the visible to the near-infrared spectral region. In this study, we propose the colorimetric determination of silver nanoprisms in microchannels using a smartphone camera. Image acquisition was performed by capturing an image of the colloidal solution of the silver nanoprisms in the microchannel using the transmitted light. Red, green, and blue chromaticity levels were extracted from the recorded images for further quantification of the silver nanoprisms. This technique was employed for the detection and colorimetric determination of hydrogen peroxide (H2 O2 ). Good linearity between the change in the green chromaticity level and concentration of hydrogen peroxide was observed for values from 10 to 300 μM with an R 2 value of 0.9670. We anticipate that the developed methodology for the quantification of silver nanoprisms and hydrogen peroxide by monitoring the change in color in the images of transmitted light will enhance the development of simple, rapid, and reliable detection systems for quality control in the production of silver nanoprisms as well as in chemical sensor applications.